Market Integration and Poverty : Evidence from South Sudan - Varela, Gonzalo; Cali, Massimiliano; Pape, Utz; Rojas, Esteban (World Bank, Washington, DC, 2016)
This paper examines the effects of market integration on household consumption using data on seven food and two energy markets across South Sudan. The analysis reveals that markets in South Sudan are highly segmented. Price differences for narrowly defined products, across cities exceed in some cases 100 percent. In addition, price volatility increased substantially following the imposition of the trade restrictions with Sudan. This increase tends to hurt disproportionately the poor, who cannot smooth purchasing decisions over time because of liquidity constraints. Transportation costs explain almost half of the variation in food prices across space, and improving the quality of roads has a large potential to reduce prices in the most expensive towns. On the basis of this price effect, the simulations suggest that bringing all road quality across states to that of primary roads can yield a reduction in poverty from the rate of 51.7 percent in 2009 to between 42.8 and 46.9 percent. These estimates have to be interpreted as conservative, as they do not take into account the second-order effects of road construction from increased trade that will result from better road connectivity.